IMPLEMENTASI KARAKTER SOPAN SANTUN MELALUI PROGRAM TAHFIDZ KELAS VI DI MI AL QUR’AN JABALKAT TULUNGAGUNG - Nafsi, Filzatun; Retno Intan Kuswari; Muhammad Saiqul Huda (STAI KH. Muhammad Ali Shodiq, 2023)
Islamic education institution has an important role in forming future generations especially in character education. In this study, researcher will discuss character education of politeness. Politeness is the main character and even this is a basic in forming the personality of students well. The research method used in this study is qualitative descriptive. Data collection techniques in this study is observation, interview and documentation. The results showed that character education of politeness in tahfidz program can be carried out with various habituations. Continuing habituation will form the character of politeness towards the children which will indirectly have Islamic personalities.